STRATEGI KOMUNIKASI DALAM PENYELENGGARAAN IBADAH HAJI UNTUK MENANGKAL DISINFORMASI DAN HOAKS - Rifa'i, Anton Bahtiar (Multazam : Jurnal Manajemen Haji dan Umrah, 2024)
Every year, the Indonesian Ministry of Religion recruits journalists from various mass media as Hajj Media Center (MCH) officers. In addition to conveying news regarding the implementation of the Hajj pilgrimage, the existence of MCH is a form of openness to public information from the Ministry of Religion as the organizer of the Hajj pilgrimage. MCH is also required to be able to counter disinformation and hoax related to the implementation of the Hajj pilgrimage. Using qualitative descriptive methods, this research is intended to observe the role of MCH in countering disinformation and hoax, especially those circulating on social media. The research results show that MCH still needs to optimize its communication strategy in countering disinformation and hoax.